Analysis on the Implementation System of Early Breastfeeding Initation by Village Midwives in Pati District - Mamik Aryani; Sri Achadi Nugraheni; Anneke Suparwati (Jurnal Manajemen Kesehatan Indonesia, 2014)
AbstrakPada tahun 2010 Kabupaten Pati berada pada urutan 16 tertinggi dari 35 kabupaten di Jawa Tengah yaitu masih >10 per 1.000 KH masih diatas target tahun 2013 Jawa Tengah sebesar 8,9 per 1.000 KH. Dengan IMD dapat menyelamatkan bayi karena Skin-to-skin akan memberikan kehangatan dan perlindungan pada bayi dan colustrum merupakan imunisasi pertama bagi bayi yang mengandung zat-zat kekebalan tubuh yang tidak tergantikan. Keberhasilan pelaksanaan inisiasi menyusui dini (IMD) sangat di pengaruhi oleh pengetahuan, sikap dan motivasi bidan atau penolong persalinan itu sendiri.Jenis penelitian adalah observasional kualitatif. Informan penelitian adalah 8 Bidan desa yang dipilih dari 2 Puskesmas, masing-masing 4 orang. Informan triangulasi adalah 8 pasien, 2 bidan koordinator dan 2 kepala Puskesmas. Data dikumpulkan dengan wawancara mendalam dan observasi terhadap pelaksanaan IMD. Pengolahan metode content analysis.Hasil penelitian menunjukkan 4 dari 8 bidan desa di polindes tidak sealu melaksanakan IMD karena pasien tidak menghendaki untuk dilakukan IMD, dan dalam pelaksanaan IMD dengan cara yang tidak tepat, kemampuan kognitif semua informan utama tentang IMD masih kurang. Dapat dilihat dari semua jawaban informan utama kurang tepat dalam menjawab tentang pengertian, manfaat dan langkah-langkah pelaksanaan IMD karena semua bidan hanya berbekal peltihan APN dan belum pernah mengikuti pelatihan manajemen laktasi karena terhambat pada dana.Pelaksanaan IMD dipolindes oleh bidan desa tidak tepat. Terdapat 7 Langkah IMD yang di keluarkan oleh Kementrian Kesehatan Republik Indonesia yang seharusnya di dilaksanakan namun oleh bidan desa dalam pelaksanaan IMD tidak dilaksanakan. Diharapkan khususnya bidan desa selalu melaksanakan IMD pada setiap menolong persalinan. AbstractInfant mortality rate (IMR) in Pati district, in 2010, was > 10 per 1000 live births. It was the highest 16 th among 35 districts in Central Java province, and it was above the target of Central Java province, 8.9 per 1000 live births. Early breastfeeding initiation (IMD) could save infants due to skin-to-skin contact (contact between mother and child skins). Skin-to-skin contact gave warmness and protection to the infants. In addition, colostrum (the first breast milk being expressed) was a first immunization for infant. It contained irreplaceable body immune elements. Successfulness of IMD was influenced by knowledge, attitude, and motivation of midwives or delivery assistants. Results of a preliminary study showed that the IMD implementation was still inadequate. Village midwives did not implement IMD when they assisted deliveries because they were not patient to wait to implement IMD. The implementation of IMD was influenced by system that included input, process, and output. This system could determine the success of IMD. Objective of this study was to analyze early breastfeeding initiation system in the village maternity policlinics (polindes) by village midwives in Pati district. This was an observational qualitative study. Study informants were 8 village midwives selected from 2 primary healthcare centers (puskesmas); 4 informants were selected from each puskesmas. Triangulation informants were 8 patients, 2 midwives coordinators, and 2 heads of puskesmas. Data were collected by conducting in-depth interview and observation toward IMD implementation. Content analysis method was applied in the data management. Results of the study showed that four of eight village midwives in the polindes did not implement IMD continuously because patients did not want to do IMD; implementation of IMD was not done properly; cognitive ability of the main informants regarding IMD was insufficient. The main informants did not answer properly questions regarding definition, benefits, and steps to do IMD. All midwives were only equipped with knowledge from APN training, and they did not receive training regarding lactation management due to funding constraint. The implementation of IMD in the polindes by village midwives was not proper. Seven steps to implement IMD issued by Ministry of Health of the Indonesian Republic were not done by village midwives. Village midwives are suggested to always implement IMD when they assist a delivery.